The Effect of ESG Disclosure, Financial Statement Quality and Debt Maturity on Investment Efficiency in Manufacturing Companies Listed on the Indonesia Stock Exchange - Cyrene Eugenia Stephanie; Putri Wahyuni (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
This study aims to determine whether ESG Disclosure, Financial Statement Quality and Debt Maturity have significant effect on Investment Efficiency in manufacturing companies listed on the Indonesia Stock Exchange. This study uses quantitative methods and the data source is secondary data. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange, totaling 249 companies. The sample in this research are 16 companies from 2019 – 2023 totaling 80 samples using purposive sampling data collection technique. Data analysis and testing consist of descriptive statistics, classical assumption tests, multiple regression analysis, partial hypothesis testing (T Test) and simultaneous hypothesis testing (F test), and the coefficient of determination test. The results of this study indicate that ESG Disclosure has no effect and is not significant on Investment Efficiency with a T count of 1.825 < T table 1.991 and a significant value of 0.072 > 0.05. The Financial Statement Quality has a partially significant effect on Investment Efficiency with a T count of 3.567 > T table 1.991 and a significant value of 0.001 < 0.05. Debt Maturity has no effect and is not significant on Investment Efficiency with a T count of 1.200 < T table 1.991 and a significant value of 0.234 > 0.05. ESG Disclosure, Financial Statement Quality, and Debt Maturity simultaneously have a significant effect on Investment Efficiency with the value of F count 4.782 > F table 2.72 and a significant value of 0.004 < 0.05. The regression coefficient value is 12.6%.